This place will become home : refugee repatriation to Ethiopia - Hammond, Laura, 1967- (Cornell paperbacks., 2004)
'This Place Will Become Home' provides insight into how people cope with extreme economic hardship, food insecurity and limited access to international humanitarian or development assistance in their struggle to attain economic self-sufficiency.